MicroRNAs Are Stored in Human MII Oocyte and Their Expression Profile Changes in Reproductive Aging. Issue 6 (1st December 2016) - Battaglia, Rosalia; Vento, Maria Elena; Ragusa, Marco; Barbagallo, Davide; La Ferlita, Alessandro; Di Emidio, Giovanna; Borzí, Placido; Artini, Paolo Giovanni; Scollo, Paolo; Tatone, Carla; Purrello, Michele; Di Pietro, Cinzia
Abstract: Maternal RNAs are synthesized by the oocyte during its growth; some of them are utilized for oocyte-specific processes and metabolism, others are stored and used during early development before embryonic genome activation. The appropriate expression of complex sets of genes is needed for oocyte maturation and early embryo development. In spite of the basic role of noncoding RNAs in the regulation of gene expression, few studies have analyzed their role in human oocytes. In this study, we identified the microRNAs (miRNAs) expressed in human metaphase II stage oocytes, and found that some of them are able to control pluripotency, chromatin remodeling, and early embryo development. We demonstrated that 12 miRNAs are differentially expressed in women of advanced reproductive age and, by bioinformatics analysis, we identified their mRNA targets, expressed in human oocytes and involved in the regulation of pathways altered in reproductive aging. Finally, we found the upregulation of miR-29a-3p, miR-203a-3p, and miR-494-3p, evolutionarily conserved miRNAs, also in aged mouse oocytes, and demonstrated that their overexpression is antithetically correlated with the downregulation of DNA methyltransferase 3A (Dnmt3a), DNA methyltransferase 3B (Dnmt3b), phosphatase and tensin homolog (Pten), and mitochondrial transcription factor A (Tfam). We propose that oocyte miRNAs perform an important regulatory function in human female germ cells, and their altered regulation could explain the changes occurring in oocyte aging.